Severe pulmonary hypertension in advanced Rheumatic heart disease: a retrospective analysis of Mitral valve replacement surgery in husm - Rahman, Aminuddin Abdul (2012)
The purpose of this study is to evaluate the improvement in patient who had mitral valve disease with severe pulmonary hypertension and the differences in the findings of preoperative and post operative echocardiography after their mitral valve replacement operations as well of the association between the PASP and NYHA class of patient. To evaluate the safety of mitral valve replacement surgery in rheumatic heart disease patients with severe pulmonary hypertension (SPH); defined as pulmonary artery systolic pressure (PASP > 60 mmHg) on patients operated for mitral valve replacement at Cardiothoracic Unit, Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan. This retrospective study on 83 patients (54 women, 29 men, mean age 39 ± 14) who had underwent mitral valve replacement surgery with or without aortic valve repair for the period of 96 months from January 2002 to December 2010. All patients underwent a complete evaluation of transthoracic echocardiography. PASP range from 60 to 135mmHg (mean 80.11 ± 19.36 mmHg). LVEF range from 22 to 77% (mean 61.62 ± 9.36 %) The predominant preoperative mitral valve lesion was mixed lesion (mitral stenosis and mitral regurgitation) in 48 patients, stenosis in 24 patients and regurgitation in 11. Nine (10.8%) underwent mitral valve replacement (MVR), 13 (15.7%) underwent dual valve replacements (DVR), 48 (57.8%) underwent mitral valve replacement with tricuspid annuloplasty (TAP), 12 (14.5%) underwent DVR with TAP and 1 (1.2%) underwent MVR with closure of atrial septal defect (ASD) Echocardiographic findings revealed there is a significant reduction in PASP postoperatively from 77.72 mmHg to 39.00mmHg (p < 0.01) Out of 83 patients, 4 (4.8%) patients had stroke within 6 month postoperatively, 2 (2.4%) had bleeding requiring hospital admissions, 2 (2.4%) had reoperations after oprations ans 2 (2.4%) had post-operative renal failure. Two (2.4%) died first two operative months. Patient in majority had NYHA II and III preoperatively showed distinct recovery and recovered well to NYHA I after 6 month operation. Mitral valve replacement can be successfully performed with an acceptable morbidity and very low mortality in patients with long standing mitral valve disease and SPH.